Prelinguistic human infants and great apes show different communicative strategies in a triadic request situation - Gretscher, Heinz (PLoS One, 2017)
In the present research, we investigate the communicative strategies of 20 month old human infants and great apes when requesting rewards from a human experimenter. Infants and apes both adapted their signals to the attentional state of the experimenter as well as to the location of the reward. Yet, while infants frequently positioned themselves in front of the experimenter and pointed towards a distant reward, apes either remained in the experimenter’s line of sight and pointed towards him or moved out of sight and pointed towards the reward. Further, when pointing towards a reward that was placed at a distance from the experimenter, only the infants, and not the apes, took the experimenter’s attentional state into account. These results demonstrate that prelinguistic human infants and nonhuman apes use different means when guiding others’ attention to a location; indicating that differing cognitive mechanisms may underlie their pointing gestures.